Pengaruh Social Media Marketing terhadap Keputusan Pembelian pada Platform Tiktok Shop : (Survei pada Mahasiswa Universitas Negeri Makassar Angkatan 2020-2023) - Bunga Nurul Qalbi; Abdi Akbar Idris; Muhammad Ilham Wardhana Haeruddin (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
This research investigates the influence of Social Media Marketing on Purchase Decisions on the TikTok Shop Platform for Makassar State University Students Class of 2020-2023. With a quantitative approach, primary data from 140 respondents was analyzed using descriptive methods, assumption testing, validity, reliability and simple linear regression. The results show that Social Media Marketing significantly influences Purchasing Decisions, with a p value = 0.01 < 0.05, a correlation coefficient of 0.741, and an R Square of 0.496, indicating an influence of 49.6%. The implications of this research support the hypothesis (H1) that Social Media Marketing has a positive and significant effect on Purchase Decisions on the TikTok Shop Platform for Makassar State University Students Class of 2020-2023.